2018
DOI: 10.1093/ajcn/nqy196
|View full text |Cite
|
Sign up to set email alerts
|

Effects of intermittent and continuous calorie restriction on body weight and metabolism over 50 wk: a randomized controlled trial

Abstract: Background Although preliminary evidence suggests that intermittent calorie restriction (ICR) exerts stronger effects on metabolic parameters, which may link obesity and major chronic diseases, compared with continuous calorie restriction (CCR), there is a lack of well-powered intervention studies. Objective We conducted a randomized controlled trial to test whether ICR, operationalized as the “5:2 diet,” has stronger effects… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
250
0
34

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 187 publications
(293 citation statements)
references
References 22 publications
9
250
0
34
Order By: Relevance
“…Furthermore, two studies related to ICR and Ramadan fasting found no changes in lipid metabolism in obese and overweight subjects. 29,37 However, this was not the case for ADF where some changes were measured. 18,32,40 There may be a number of reasons for the differences reported on the effects of IF.…”
Section: Fasting Protocols and Metabolic Adaptationsmentioning
confidence: 99%
“…Furthermore, two studies related to ICR and Ramadan fasting found no changes in lipid metabolism in obese and overweight subjects. 29,37 However, this was not the case for ADF where some changes were measured. 18,32,40 There may be a number of reasons for the differences reported on the effects of IF.…”
Section: Fasting Protocols and Metabolic Adaptationsmentioning
confidence: 99%
“…Considering the limited evidence from human studies, it was the aim of this cross-sectional study to evaluate associations between food consumption and liver fat content. We used baseline data from the Healthy Nutrition and Energy Restriction as Cancer Prevention Strategies: A Randomized Controlled Intervention Trial (HELENA Trial) [15], a randomized controlled intervention study, in a post-hoc manner to evaluate food frequency questionnaire-(FFQ-) derived dietary items (47 food groups and two diet quality scores, the MED diet and DASH scores) in relation to liver fat content measured by magnetic resonance imaging (MRI) among 136 overweight or obese individuals.…”
Section: Introductionmentioning
confidence: 99%
“…Intermittent fasting helps reduce weight and can contribute to good health, but not better than regular diets (116). This is the conclusion reached by the scientists from the German Cancer Research Centre (DKFZ) and the Heidelberg University Hospital (Deutsches Krebsforschungszentrum und das Universitätsklinikum Heidelberg) in the HELENA study (HELENA-Studie) (116), the largest study in this area to date. It is obvious to researchers that there are many different ways to reduce weight, but it is important to select the right option for each patient.…”
Section: N T E R M I T T E N T F a S T I N G D I E T ( 5 : 2 ) ( I mentioning
confidence: 97%
“…Due to the high hopes that some dieticians and sports physicians have today for the intermittent fasting, it is of great interest to researchers to compare different forms of diet in terms of the weight loss (116,117,118).…”
Section: N T E R M I T T E N T F a S T I N G D I E T ( 5 : 2 ) ( I mentioning
confidence: 99%